Method for producing polyamide resin film

By regenerating monomers from waste polyamide resin and polymerizing them into a film, the method addresses the challenges of productivity and printing quality in existing polyamide resin film production, achieving enhanced mechanical and environmental performance.

JP2025071121APending Publication Date: 2025-05-02UNITIKA LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2025021342
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-01-24
Filing Date
2025-02-13
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing methods for producing polyamide resin films using recycled materials face challenges such as increased foreign matter and thermal degradation, leading to reduced productivity and poor printing and adhesion properties.

Method used

A method involving the depolymerization of waste polyamide resin to regenerate monomers, which are then polymerized to produce a polyamide resin film. This film is further processed through stretching and refinement to achieve improved printing suitability and mechanical properties.

Benefits of technology

The resulting polyamide resin film exhibits printing suitability comparable to or better than conventional films, with improved mechanical properties and a high recycle ratio, promoting environmental sustainability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025071121000004
    Figure 2025071121000004
  • Figure 2025071121000001
    Figure 2025071121000001
  • Figure 2025071121000002
    Figure 2025071121000002
Patent Text Reader

Abstract

To provide a method for producing a polyamide resin film by using a polyamide resin obtained through polymerization of a regenerated monomer as a recycled material.SOLUTION: The method for producing a polyamide resin film comprises: (1) a step for generating a monomer from a depolymerization material (A); (2) a step for producing a polyamide resin (B) through polymerization using a material containing the monomer; (3) a step for refining the polyamide resin (B); and (4) a step for preparing an unstretched film by using a starting material containing the refined polyamide resin (B), and then stretching the unstretched film.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a polyamide resin film containing a polyamide resin using a large amount of recycled raw materials. [Background technology]

[0002] Environmental issues have been attracting attention for a long time, but in recent years, awareness of ensuring environmental sustainability has been on the rise. There has long been a demand for recycling waste resins, and these are used as raw resin materials. For example, waste materials generated during the production of stretched thermoplastic resin films include waste materials such as trimmed edges and slits, as well as films that were not commercialized as defective products. Material recycling is commonly carried out by melting these materials again to create pellets that are then used as remelted resin (raw material).

[0003] However, in material recycling, the content of foreign matter, heat-degraded materials, etc. increases with an increase in the content of remelted resin, and therefore, in particular, in polyamide resin films with large stretching stress, they tend to break during stretching, which reduces productivity. Moreover, since it becomes difficult to control the amount of additives contained in the remelted resin, local property changes occur even on the film surface, which can lead to printing defects, adhesion defects, etc. As such, the amount of remelted resin that can be contained in a polyamide resin film is limited, and it is said that there is a limit to increasing the recycling rate.

[0004] On the other hand, laminated films, such as packaging films, in which multiple types of resin raw materials are laminated, such as a printing layer, a barrier layer, an adhesive layer, and a sealant layer, can be difficult to separate into each raw material and can be difficult to recycle.

[0005] In such cases, a method is known in which waste resin is depolymerized and used as a monomer (regenerated monomer), which is also called chemical recycling. In particular, various chemical recycling methods have been proposed for polyamide resins. For example, a method is known in which nylon 6 is melted, metals are removed, and ε-caprolactam obtained by the depolymerization reaction is recovered and used as a fiber raw material, a resin raw material, etc., and the recovered ε-caprolactam can be reused (Patent Document 1, Patent Document 2). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 7-330718 [Patent Document 2] China Publication Bulletin CN91106147.9 Summary of the Invention [Problem to be solved by the invention]

[0007] However, even if a monomer obtained by depolymerizing waste polyamide resin is polymerized, a polyamide resin suitable for a film cannot be obtained, i.e., a film having excellent strength, elongation, etc. cannot be obtained.

[0008] Moreover, in recent years, a wide variety of printing has been applied to product packages such as wrapping containers, and there is a tendency for demands for printed appearance to be increasing, leaving room for improvement in the printability of film (especially the reproducibility of light areas (low gradation areas) in the expression of light and dark shades).

[0009] Therefore, the main object of the present invention is to provide a method for producing a polyamide resin film using a polyamide resin obtained by polymerizing a recycled monomer as a recycled raw material. Another object of the present invention is to provide a polyamide resin film that can exhibit printability and the like equal to or better than that of conventional products. [Means for solving the problem]

[0010] As a result of extensive research in light of the problems in the prior art, the inventors discovered that the above-mentioned objective could be achieved by using specific raw materials containing recycled monomers in the production of film, and thus completed the present invention.

[0011] That is, the present invention relates to the following polyamide resin and a method for producing the same. 1. A method for producing a polyamide resin film, comprising: (1) a step of producing a monomer from a raw material for depolymerization (A); (2) producing a polyamide resin (B) by polymerizing a raw material containing the monomer; (3) A step of refining the polyamide resin (B) (4) A step of producing an unstretched film using a starting material containing the refined polyamide resin (B) and then stretching the unstretched film. A method for producing a polyamide resin film, comprising: 2. The method according to item 1, wherein the monomer comprises ε-caprolactam. 3. The method according to item 1, further comprising a step of adjusting the moisture content of the unstretched film to 2 to 10% by mass prior to the stretching. 4. The method according to claim 1, wherein a remelted resin obtained by melting a polyamide resin (excluding the polyamide resin (B)) is contained as part of the starting material, and the content of the remelted resin is 1 mass% or more. 5. The method according to item 1, wherein the refined polyamide resin (B) has a relative viscosity ηR of 2.5 to 4.5. 6. The production method according to item 1, wherein the raw material for depolymerization (A) is at least one of a polyamide 6 resin and an oligomer thereof. 7. 1000mm of half-tone printing 10% gradation on film 2 Polyamide resin film with 100 or less missing dots. 8. The polyamide resin film according to item 7, wherein the caprolactam monomer concentration in the polyamide resin film is 1.6 mass% or less. 9. The polyamide resin film according to item 7, wherein the content of each of the amino terminal group and the carboxyl terminal group in the polyamide resin film is 80 mmol / kg or less. 10. The polyamide resin film according to item 7, wherein the ratio of the minimum value to the maximum value of the film impact strength (minimum value / maximum value) in an atmosphere having a temperature of 23° C. and a humidity of 50% RH is 0.5 to 1.0. 11. The polyamide resin film according to item 7, comprising a polyamide resin having a half-value width of a temperature-lowering crystallization peak of 10° C. or more. 12. The polyamide resin film according to claim 7, which is biaxially oriented. 13. A laminate film comprising the polyamide resin film according to any one of items 7 to 12 and a sealant resin layer laminated on the polyamide resin film. 14. A packaging material comprising the polyamide resin film according to any one of items 7 to 12. 15. A polyamide resin film obtained by the production method according to any one of items 1 to 6. Effect of the Invention

[0012] According to the present invention, even if a polyamide resin obtained by polymerizing a recycled monomer is used as a recycled raw material, a polyamide resin film that can exhibit printability and the like equal to or better than that of a conventional product (new product) can be provided. More specifically, in the present invention, by using a polyamide resin made from a recycled monomer as a raw material, a polyamide resin film (particularly a biaxially oriented polyamide resin film) can be provided in which localized deterioration in print appearance, deterioration in adhesion, and the like are effectively suppressed.

[0013] Moreover, the polyamide resin film of the present invention has controlled variations in impact strength and is excellent in general physical properties such as film elongation, wettability, and haze, and is therefore particularly suitable for use as a packaging material.

[0014] In the manufacturing method of the present invention, waste resin materials can be used as raw materials, so that a recycled polyamide resin film with a high recycling rate of, for example, 50% or more can be provided. This promotes the reuse of resources, and can contribute to environmental conservation as a sustainable technology. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a diagram showing an outline of a method for evaluating the printability of a polyamide resin film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] 1. Manufacturing method of polyamide resin film The manufacturing method of the present invention is a method for manufacturing a polyamide resin film, comprising the steps of: (1) A step of producing a monomer from a raw material for depolymerization (A) (depolymerization step); (2) A step of producing a polyamide resin (B) by polymerizing a raw material containing the monomer (polymerization step); (3) A step of refining the polyamide resin (B) (refining step) (4) A process for producing an unstretched film using a starting material containing the refined polyamide resin (B), and then stretching the unstretched film (film formation process) Characterized in that it comprises

[0017] Depolymerization process In the depolymerization step, a monomer is regenerated from the raw material for depolymerization (A) (hereinafter, such a monomer is referred to as a "regenerated monomer").

[0018] As the regenerated monomer, lactams are particularly preferred, such as ε-caprolactam, enantholactam, capryllactam, lauryllactam, etc. Among these, ε-caprolactam is particularly preferred.

[0019] The type of the raw material for depolymerization (A) is not particularly limited, and in addition to various polyamide resins, oligomers of various polyamide resins can also be used. More specifically, the various resins listed as polyamide resins (B) described later can be exemplified. In addition, examples of the oligomer include linear bodies of about dimer to about heptamer, and cyclic bodies of about dimer to about nonamer.

[0020] In particular, in the present invention, at least one of polyamide 6 resin and its oligomer can be suitably used as the raw material for depolymerization (A). In particular, polyamide 6 is a resin substantially composed of ε-caprolactam alone as a monomer unit, and therefore has the advantage of being easy to monomerize and purify and separate.

[0021] Examples of the form of polyamide resin include discharged resin waste, including waste from switching between brands during polymerization and waste from switching up to the commercialization of film products, waste waste such as edge trimming waste and slit waste generated during film production, and films that were not commercialized as defective products, etc. Using these as raw materials not only contributes to the production of films with excellent printability, but also contributes to environmental conservation by utilizing waste materials.

[0022] Examples of the form of the oligomer include not only highly water-soluble oligomers recovered from the refining water generated during the refining of polyamide resin, but also residues after filtration containing dimers to octamers with low water solubility.

[0023] The method for producing a monomer from the raw material for depolymerization (A) is not particularly limited as long as a predetermined monomer can be obtained, but preferably, a depolymerization reaction of the raw material for depolymerization (A) can be adopted. That is, the raw material for depolymerization (A) can be chemically decomposed by the depolymerization reaction to suitably produce a regenerated monomer.

[0024] The method and conditions of the depolymerization reaction are not particularly limited, and the depolymerization reaction can be carried out according to a known method. Therefore, for example, a catalyst may be used or may not be used. The depolymerization may be carried out in the absence of water (dry type) or in the presence of water (wet type). In particular, from the viewpoint of productivity, a method in which the depolymerization is carried out in hot steam in the presence of a catalyst is preferred. Although it is difficult to directly depolymerize cyclic oligomers with low water solubility due to the slow hydrolysis rate of the amide bond, it is possible to suitably obtain regenerated monomers from cyclic oligomers by ring-opening polymerization to form chain molecules and then depolymerizing them under the above-mentioned conditions.

[0025] Polymerization process In the polymerization step, a polyamide resin (B) is produced by polymerization using a raw material containing the monomer (recycled monomer).

[0026] The raw material may be a raw material in which all monomers are recycled monomers, but it is preferable to use virgin monomers in combination. Here, the term "virgin monomer" is the antonym of "recycled monomer" and refers to a monomer that has not undergone a polymer depolymerization process. Commercially available virgin monomers can also be used. For example, monomers that are normally commercially available can be used as virgin monomers.

[0027] Recycled monomers may contain by-products that are difficult to separate. This allows the crystallization rate of polyamide resins made only from recycled monomers to be slightly slower than that of polyamide resins made only from virgin monomers, and the crystallization rate of polyamide resins polymerized using a combination of recycled and virgin monomers can be further slowed. This crystallization rate is determined by the cooling crystallization temperature (T C) was measured, and the half-width of the crystallization peak obtained was used as an index. The half-width in the present invention is usually preferably 10°C or more, more preferably 11°C or more, and most preferably 12°C or more. The wider the half-width, the wider the crystallization speed, and when the film is stretched and crystallized, the less likely local unevenness in the crystalline state of the film surface will occur, which can improve uniformity and ultimately improve the printability of low gradation parts. From this perspective, it is preferable to use a polyamide resin polymerized by using a combination of recycled monomers and virgin monomers. The upper limit of the half-width can be, for example, about 20°C, but is not limited thereto.

[0028] The content of the recycled monomer in the raw material is not particularly limited, but from the viewpoint of widening the half-value width, the upper limit is preferably 90% by mass or less, and more preferably 80% by mass or less. Also, the lower limit is not particularly limited, but from the viewpoint of increasing the recycle ratio, it is preferably 5% by mass or more, and particularly preferably 10% by mass or more.

[0029] As a component other than the recycled monomer, it is preferable to use a virgin monomer in combination. In this case, the content of the virgin monomer in the raw material is usually preferably about 10 to 95 mass %, and more preferably 20 to 90 mass %.

[0030] For example, it is possible to use ε-caprolactam (hereinafter referred to as "C-CL") regenerated by the depolymerization reaction of polyamide 6 resin in a range close to 100 mass% in the monomers, but it is preferable to contain ε-caprolactam (hereinafter referred to as "V-CL") as a virgin monomer as a monomer other than C-CL.

[0031] In addition, the polyamide resin (B) may be end-blocked as necessary for the purpose of suppressing monomer generation during melting. For this reason, the raw material may contain additives such as end-blocking agents as necessary. The end-blocking agents are not particularly limited, and examples thereof include organic glycidyl esters, dicarboxylic anhydrides, monocarboxylic acids such as benzoic acid, and diamines.

[0032] The polymerization method for obtaining the polyamide resin (B) is not particularly limited, and a known method for polymerizing a monomer can be adopted. For example, a method can be adopted in which ε-caprolactam, water, and benzoic acid as an end-capping agent are mixed, heated and pressurized in a polymerization vessel, and then the mixture is depressurized and dehydrated while undergoing a polymerization reaction until the desired viscosity is reached.

[0033] Scouring process In the refining step, the polyamide resin (B) is refined, whereby monomers contained in the polyamide resin are removed and the relative viscosity of the polyamide resin can be increased to a desired range, resulting in physical properties suitable for film formation.

[0034] The method of scouring is not limited, but it is particularly preferable to perform scouring so that the relative viscosity (25°C) of the polyamide resin (B) falls within the range of about 2.5 to 4.5. Therefore, for example, it is preferable to perform scouring using hot water at 90 to 100°C for about 15 to 30 hours.

[0035] The refining method itself can be a known method such as immersing the polyamide resin (B) in hot water. In this case, the polyamide resin (B) can be refined in the form of a molded product such as pellets.

[0036] The refining step may be a single treatment, but may be performed twice or more as necessary. By performing the refining sufficiently, the monomer contained in the polyamide resin can be more completely dissolved in hot water, so that the monomer content in the polyamide resin after refining can be sufficiently reduced.

[0037] The polyamide resin after the refining step is preferably dried as necessary. The drying conditions are not particularly limited. For example, hot air drying can be performed at about 100 to 130°C for about 10 to 30 hours, but is not limited thereto. More specifically, hot air drying can be performed at 110°C for 20 hours.

[0038] Film making process In the film-forming step, an unstretched film is produced using a starting material containing the refined polyamide resin (B), and then the unstretched film is stretched.

[0039] The starting material may contain polyamide resin (B), but may contain other components as necessary. For example, in order to increase cost benefits, recycling rate, etc., a remelted resin (D) obtained by melting a polyamide resin (excluding the polyamide resin (B)) may be contained within a range that does not impede the effects of the present invention. In the present invention, from the viewpoint of environmental conservation and effective use of resources, waste resin of polyamide resin (particularly polyamide 6 resin) can be suitably used as the remelted resin (D). More specifically, pellets formed by remelting unstretched scraps, edge trimming scraps, slit scraps, defective products, etc. generated during the production of polyamide resin films can be mentioned.

[0040] The content of the remelted resin (D) in the starting material is not particularly limited, but is preferably 1% by mass or more, and more preferably 5% by mass or more, from the viewpoint of increasing the recycling ratio. On the other hand, the upper limit of the content of the remelted resin (D) may be usually 75% by mass or less, particularly 65% ​​by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less, and most preferably 35% by mass or less. The remelted resin has a tendency to increase the amount of molecular chain terminals and decrease in viscosity, and is also inferior in quality stability. Therefore, when the content exceeds 75% by mass, in addition to a decrease in relative viscosity as a film raw material, foreign matter, heat deterioration products, etc. increase, and troubles such as cutting tend to occur during film formation. In addition, the mechanical properties of the film tend to decrease, such as a decrease in tensile elongation. In addition, the content of oligomers such as caprolactam monomers and dimers generated in the stretching process increases, which causes problems such as a local decrease in printability in the subsequent process and an increase in the rate of bag breakage due to a decrease in adhesion, and there are concerns about the impact on practical performance.

[0041] Film scraps, defective products, etc. used as remelted resin usually contain additives such as lubricants and antioxidants, and the above content includes the content of these additives.

[0042] The film scraps, defective products, etc. used as the remelted resin have different concentrations of additives such as lubricants and antioxidants depending on the brand, etc. Therefore, as the content of the remelted resin in the polyamide resin film increases, the haze of the obtained film, the wet tension of the film surface, the printability, the adhesion, etc. may be locally decreased due to the variation in the concentration distribution of the additives. For this reason, when the polyamide resin film is composed of multiple layers, the content of the remelted resin in the surface layer (outermost layer) is preferably 50 mass% or less, more preferably 40 mass% or less, and most preferably 35 mass% or less.

[0043] On the other hand, in the intermediate layer (layers other than the outermost layer), even if the remelted resin content is high, it does not affect the film surface properties such as wet tension and printability, so the remelted resin content can be increased to increase the recycling ratio. However, since there is a tendency for the film haze to increase and physical properties such as impact strength to deteriorate, it is preferable that the remelted resin content in the intermediate layer is 75% by mass or less. The lower limit of the remelted resin content in each layer can be, for example, about 5% by mass, but is not limited thereto.

[0044] As other components contained in the starting material, for example, polyamide resin (C) obtained by polymerization of raw materials consisting only of virgin monomers without containing recycled monomers may be contained.

[0045] When a mixture of polyamide resin (B) polymerized only from recycled monomers and polyamide resin (C) polymerized only from virgin monomers is used as the starting material and melt-extruded, it is possible to obtain physical properties similar to those of polyamide resin (B) polymerized using a combination of recycled monomers and virgin monomers, but from the viewpoint of obtaining more uniform film surface properties, it is preferable to polymerize using a combination of recycled monomers and virgin monomers. In other words, polyamide resin (B) composed of a polymer containing recycled monomers and virgin monomers as monomer units can be preferably used.

[0046] The relative viscosity of each polyamide resin contained in the starting material is not limited, but is preferably 2.5 to 4.5, more preferably 2.8 to 4.0. When a polyamide resin with a relative viscosity of less than 2.5 is used, film formation and stretching become difficult, and even if a polyamide resin film is obtained, the mechanical properties may be significantly reduced. In addition, when a polyamide resin with a relative viscosity of more than 4.5 is used, the film formability may be impaired.

[0047] In the present invention, the relative viscosity is a value measured by dissolving a resin to be measured in 96% sulfuric acid to a concentration of 1.0 g / dl (liquid temperature: 25° C.) using an Ubbelohde viscometer.

[0048] In addition, if necessary, one or more of various additives such as antioxidants, ultraviolet absorbers, preservatives, antistatic agents, antiblocking agents, inorganic fine particles, etc. can be added to the starting materials within a range that does not adversely affect the performance of the film.

[0049] A lubricant may be blended in the starting material for the purpose of improving the slip property of the resulting film. As the lubricant, both inorganic and organic lubricants can be used. Specific examples of the lubricant include clay, talc, calcium carbonate, zinc carbonate, wollastonite, silica, alumina, magnesium oxide, calcium silicate, sodium aluminate, calcium aluminate, magnesium aluminosilicate, glass balloon, carbon black, zinc oxide, antimony trioxide, zeolite, hydrotalcite, layered silicate, ethylene bis stearic acid amide, and the like. Among them, silica is particularly preferred. The content of the lubricant is not particularly limited, but is suitably in the range of 0.01 to 0.3 mass% in the starting material.

[0050] The method for producing the unstretched film is not limited, and the unstretched film can be formed by a known film forming method. For example, the unstretched film can be obtained by extruding the melt of the raw material from a T-die and then cooling it with a casting roll. In this case, it is necessary to precisely control the actual temperature of the casting roll surface in order to make the crystallinity of the unstretched film uniform.

[0051] In the present invention, it is preferable to adjust the moisture content of the unstretched film to about 2 to 10% by mass (particularly 4 to 8% by mass) as a moisture adjustment step as necessary before stretching. If the moisture content is lower than 2% by mass, the stretching stress increases and problems such as film breakage are likely to occur. If the moisture content is higher than 10% by mass, the thickness unevenness of the unstretched film becomes large, and the thickness unevenness of the obtained stretched film also becomes large.

[0052] In the moisture adjustment step, when the moisture content of the film is low (particularly when it is less than 2% by mass), the film is passed through a moisture adjustment tank at a temperature of 40 to 90°C, more preferably a moisture adjustment tank at a temperature of 50 to 80°C, and the moisture content of the film is adjusted by adjusting the passage time. Pure water is usually used in the moisture adjustment tank, but the processing liquid may contain dyes, surfactants, plasticizers, etc., as necessary. The moisture may also be adjusted by spraying water vapor. On the other hand, when the moisture content of the film is high (particularly when it exceeds 10% by mass), the film may be passed through a drying oven and the passage time may be adjusted.

[0053] Next, the unstretched film is stretched. The stretching method is not particularly limited, and any stretching method can be used. In particular, it is preferable to perform biaxial stretching from the viewpoint of obtaining a film having excellent tensile elongation in both the MD and TD directions.

[0054] The biaxial stretching method is not limited, and examples thereof include simultaneous biaxial stretching and sequential biaxial stretching. For example, the simultaneous biaxial stretching method is preferred from the viewpoint of surface balance, that is, reducing the difference between the MD and TD directions in physical properties such as tensile elongation, elastic modulus, and tensile strength, while the sequential biaxial stretching method is preferred from the viewpoint of improving puncture strength and impact strength. These stretching methods can be appropriately selected depending on the desired film physical properties, applications, etc.

[0055] The stretching ratio can be appropriately set depending on, for example, the application, the desired physical properties, etc., and can be, for example, 2 to 4 times in the MD direction and 2 to 4 times in the TD direction, but is not limited thereto. The stretching temperature is also not limited, and can be, for example, within the range of 40 to 220°C. In particular, in the case of sequential stretching, it is preferable that the stretching temperature in the MD direction is 40 to 80°C, and the stretching temperature in the TD direction is 80 to 150°C. In addition, in the case of simultaneous biaxial stretching, it is preferable that the temperature is 160 to 220°C.

[0056] The obtained biaxially stretched film is preferably subjected to a heat treatment at a temperature of about 150 to 220° C. for a short time, if necessary, in order to improve dimensional stability and suppress hot water shrinkage.

[0057] The polyamide resin film of the present invention may be subjected to a surface treatment such as a corona discharge treatment or an adhesion enhancing treatment, as long as the effect of the present invention is not impaired. In addition, for example, an adhesion enhancing layer, a barrier coat layer, a printed layer, etc. may be appropriately provided as necessary.

[0058] The polyamide resin film of the present invention thus obtained can also be provided as a laminate in which it is laminated with other layers as required.

[0059] Also, a film composed of multiple layers may be formed by simultaneous melt extrusion, lamination, etc., during the production stage of the polyamide resin film. For example, a two-type two-layer structure in which a polyamide resin film containing a polyamide 6 resin polymerized from recycled monomers and a polyamide 6 resin film containing a remelted resin are laminated, or a two-type three-layer structure in which a polyamide 6 resin film containing a remelted resin is sandwiched between polyamide resin films containing a polyamide 6 resin polymerized from recycled monomers, etc. may be used. If the polyamide 6 resin film has a layer structure in which an intermediate layer can be sandwiched, such as a two-type three-layer structure, the remelted resin content of the intermediate layer can be increased.

[0060] 2. Polyamide resin film The present invention is a method for producing a 1000 mm film of a halftone printed 10% gradation area. 2The polyamide resin film includes a polyamide resin film having 100 or less missing dots.

[0061] (1) Composition of polyamide resin film The composition of the polyamide resin is not particularly limited, and examples thereof include polyamide 6 resins in which lactams such as ε-caprolactam are used as monomers. Other examples of the polyamide resins include polyamide resins obtained by polycondensation of lactams having three or more ring members, ω-amino acids, dibasic acids, diamines, and the like.

[0062] More specifically, examples of lactams include, in addition to the above-mentioned ε-caprolactam, enantholactam, capryllactam, lauryllactam, and the like.

[0063] Examples of the ω-amino acids include 6-aminocaproic acid, 7-aminoheptanoic acid, 9-aminononanoic acid, and 11-aminoundecanoic acid.

[0064] Examples of dibasic acids include adipic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecadioic acid, hexadecadioic acid, eicosanedionic acid, eicosadienedioic acid, 2,2,4-trimethyladipic acid, terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, and xylylenedicarboxylic acid.

[0065] Examples of diamines include ethylenediamine, trimethylenediamine, tetramethylenediamine, hexamethylenediamine, pentamethylenediamine, undecamethylenediamine, 2,2,4 (or 2,4,4)-trimethylhexamethylenediamine, cyclohexanediamine, bis-(4,4'-aminocyclohexyl)methane, metaxylylenediamine, nonanediamine, and decanediamine.

[0066] Examples of the polymer or copolymer obtained by polycondensation of these include polyamide 6, 7, 10, 11, 12, 4.10, 5.6, 6.6, 6.9, 6.10, 6.11, 6.12, 10.10, 6T, 9T, 10T, 6I, MXD6 (meta-xylylene dipanamide 6), 6 / 6.6, 6 / 12, 6 / 6T, 6 / 6I, 6 / MXD6, etc. Among them, polyamide 6 resin is preferred in the present invention because it has an excellent balance between heat resistance and mechanical properties. That is, polyamide 6 resin film is preferred as the polyamide resin film of the present invention.

[0067] (2) Physical properties of polyamide resin film The polyamide resin film of the present invention has a 1000 mm gradation of a halftone printed 10% gradation area on the film. 2 It has a printing suitability of 100 or less missing dots. A film with such characteristics is advantageous for printing in that it has high reproducibility in the appearance of the print, especially in the light parts of the shade. The number is particularly preferably 80 or less, more preferably 70 or less, and most preferably 60 or less. If the number exceeds 100, even in the low gradation part, unevenness can be visually confirmed when looking closely, individual differences in the pattern can be felt, and it may be judged as a printing defect. It is most preferable that the lower limit of the number is 0, but it may be about 30, for example, but is not limited to this.

[0068] The polyamide resin film of the present invention preferably has a relative viscosity ηR of 2.5 to 4.5, more preferably in the range of 2.8 to 4.0. The relative viscosity in the present invention is a value measured by using an Ubbelohde viscometer for a sample solution (liquid temperature 25°C) in which the film to be measured is dissolved in 96% sulfuric acid to a concentration of 1.0 g / dl. A polyamide resin film having a relative viscosity of less than 2.5 may have significantly reduced mechanical properties or may have a reduced evaluation in the drop bag test of the laminated film described below. A polyamide resin film having a relative viscosity of more than 4.5 may have insufficient uniformity in the film thickness, resulting in uneven mechanical properties.

[0069] The thickness accuracy of the polyamide resin film of the present invention is preferably within ±15% of the target thickness, and more preferably within ±10%.

[0070] The polyamide resin film of the present invention preferably has an extractable amount of caprolactam monomer of 1.6% by mass or less, more preferably 1.0% by mass or less, even more preferably 0.5% by mass or less, and most preferably 0.1% by mass or less. If the extractable amount of caprolactam monomer exceeds 1.6% by mass, the wettability of the polyamide resin film surface tends to vary. In addition, the adhesion between the polyamide resin film and other resin layers or inks may be locally reduced, which may result in a reduction in practical performance, such as the number of times until the bag breaks in a bag drop test.

[0071] The polyamide resin film of the present invention preferably has an amino end group and a carboxyl end group content of 80 mmol / kg or less, and most preferably 70 mmol / kg or less. If the amino end group and the carboxyl end group content exceed 80 mmol / kg, respectively, the crystallization rate of the film increases, and local variations in crystallinity are likely to occur. This leads to a decrease in the local printability of the film, as well as a decrease in tensile elongation and a decrease in physical properties such as impact strength, which may be partially reduced.

[0072] The polyamide resin film of the present invention preferably has a ratio of the minimum value to the maximum value of the film impact strength (minimum value / maximum value) in an atmosphere at a temperature of 23° C. and a humidity of 50% RH of 0.5 to 1.0, more preferably 0.6 to 1.0, and most preferably 0.7 to 1.0. If the ratio is less than 0.5, it is considered that there is a partial decrease in the impact resistance of the film, which is not practically preferable.

[0073] The polyamide resin film of the present invention preferably has a tensile elongation in both the MD and TD directions of 60% or more, and more preferably 70% or more.

[0074] The polyamide resin film of the present invention preferably has a haze value of 10.0% or less, more preferably 7.0% or less, and most preferably 6.0% or less.

[0075] The polyamide resin film of the present invention is preferably a film obtained by the above-mentioned "1. Method for producing polyamide resin film". In other words, it is preferable that the film is produced using raw materials containing recycled monomers. Therefore, the polyamide resin film of the present invention is preferably a stretched film (particularly a biaxially stretched film). This makes it possible to more reliably obtain the above-mentioned physical properties.

[0076] Therefore, the polyamide resin film of the present invention may be a polyamide resin film obtained by polymerizing a recycled monomer alone, may be a mixture of two or more kinds, or may be a polyamide resin film containing a remelted resin described later. It may also be a film composed of a single layer, or may be a film composed of multiple layers formed by simultaneous melt extrusion or lamination. For example, it may be a two-layer structure in which a polyamide resin film containing a polyamide resin polymerized with a recycled monomer and a polyamide resin film containing a remelted resin are laminated, or a three-layer structure in which a polyamide resin film containing a remelted resin is sandwiched between polyamide resin films containing a polyamide resin polymerized with a recycled monomer. When composed of multiple layers, it is preferable that at least one of the outermost layers contains a polyamide resin polymerized with a recycled monomer.

[0077] (3) Use of polyamide resin film The polyamide resin film of the present invention (particularly the biaxially stretched polyamide resin film) obtained as described above has excellent mechanical properties such as tensile elongation, tensile strength, and elastic modulus as a polyamide resin film, as well as excellent transparency, color tone, wettability, printability, and the like, and is therefore particularly suitable for use as a packaging material.

[0078] The polyamide resin film of the present invention can be used alone or in the form of a laminate by laminating it with other layers. For example, an easy-adhesion layer, a barrier coat layer, a printing layer, an adhesive layer, etc. can be appropriately provided as necessary.

[0079] The polyamide resin film of the present invention can be laminated with a sealant layer such as polyolefin by a known method such as dry lamination or extrusion lamination to form a laminated film, and the opposing sealant layers can be heat-sealed to each other to be used as a packaging bag (bag body). As the bag body, any of the following forms can be used: two-sided bag, three-sided bag, palm-shaped bag, gusset bag, side-seal bag, stand bag, stand zipper bag, etc.

[0080] There are no limitations on the items (contents) to be packaged, and the material can be used for a wide range of purposes, including packaging food and drink, medicines, cosmetics, chemicals, and miscellaneous goods.

[0081] The present invention also includes a laminated film comprising the polyamide resin film of the present invention and a sealant resin layer laminated on the polyamide resin film. Such a laminated film can also be suitably used as a packaging material or package. The polyamide resin film of the present invention has a uniform surface state, and additives, monomers, etc. are rarely precipitated locally, and there is no local decrease in adhesion, so the resulting package has excellent resistance to bag breakage. For example, when a package filled with water is broken by dropping, it may not only break from the part with low strength, but also delaminate from the part with low local adhesion, causing the bag to break. In contrast, the laminated film of the present invention has the advantage of being less prone to bag breakage than a ready-made product.

[0082] More specifically, in a bag drop test under an atmosphere of 25°C and 55% RH, the laminated film of the present invention is preferably dropped 50 times or more before breaking, more preferably 60 times or more, and even more preferably 70 times or more. The bag drop test is carried out by dropping a package filled with 1000 ml of water and 10 ml of air (two 200 mm x 300 mm laminates heat-sealed at a width of 10 mm) from a height of 1.2 m. EXAMPLES

[0083] The features of the present invention will be described in more detail below with reference to examples and comparative examples, although the scope of the present invention is not limited to the examples.

[0084] 1.Ingredients used The raw materials used in the examples and comparative examples are as follows. Table 1 shows the time required for the polymerization reaction and the total refining processing time in the preparation of each raw material, as well as the relative viscosity (ηR), crystallization temperature (Tc) and its half-width, and monomer content (caprolactam content) of the obtained raw materials.

[0085] Raw materials B2~B4 Film scraps or defective products generated during the production of polyamide 6 resin films and resin scraps (resin waste materials) containing oligomers generated during the polymerization of polyamide 6 resin were used as the raw material for depolymerization (A). Phosphoric acid was added to the raw material for depolymerization (A) and a depolymerization reaction was carried out under heating using a wet method. After purification by activated carbon treatment, concentration, and distillation, the regenerated ε-caprolactam "C-CL" was recovered. On the other hand, "V-CL" is ε-caprolactam, a virgin monomer. C-CL and V-CL were blended to the ratio (mass ratio) in Table 1, and mixed with water and benzoic acid as an end-capping agent. The mixture was heated, pressurized, depressurized, and dehydrated in a polymerization kettle, and then polymerized until the target viscosity was reached. The polymerization time required for the final target viscosity differs depending on the ratio of CL species. Each polymerization time is as shown in Table 1. The obtained polymer (resin) was pelletized, and then refined by hot water treatment at 95°C twice in total for 10 hours and 15 hours, and then dried at 110°C for 20 hours. In this way, polyamide resins (raw materials B2 to 4) with a relative viscosity of 3.1 were obtained.

[0086] Raw materials B1, B5 Using C-CL, water, and benzoic acid as an end-capping agent as the raw materials, the polymer was polymerized in the same manner as above, pelletized, and refined twice in hot water at 95° C. for 10 hours and 15 hours, and then dried at 110° C. for 20 hours. In this way, polyamide resin (B1) with a relative viscosity of 3.0 was obtained. In addition, the polyamide resin (B1) was polymerized under the same conditions as those for the polyamide resin (B1), pelletized, refined by hot water treatment at 95° C. for 18 hours, and then dried at 110° C. for 20 hours. In this way, a polyamide resin (raw material B5) having a relative viscosity of 2.7 was obtained.

[0087] Raw material B6 Polymerization was carried out under the same conditions as for raw material B1, pelletization was performed, and the mixture was refined by hot water treatment at 95° C. for 10 hours, and then dried at 110° C. for 20 hours. Thus, a polyamide resin (raw material B6) having a relative viscosity of 2.4 was obtained.

[0088] Raw material C Using V-CL, water, and benzoic acid as an end-capping agent as raw materials, the polymer was polymerized in the same manner, pelletized, and refined twice by hot water treatment at 95°C for 10 hours and 10 hours each, and then dried at 110°C for 20 hours. In this way, a polyamide resin (raw material C) with a relative viscosity of 3.1 was obtained.

[0089] Raw material D Film scraps generated during the production of polyamide 6 resin film were crushed, remelted at 250 to 290°C, and pelletized. Then, the pellets were dried. In this way, a remelted resin (raw material D) was obtained. The relative viscosity of the remelted resin was 2.9.

[0090] Silica Master E (silica-containing polyamide resin, contains 6% silica by mass) The master chip was made of PCM-30 manufactured by Ikegai Seisakusho, and was charged from the supply port so that A1030BRF (polyamide 6 resin manufactured by Unitika) / silica 1 (manufactured by Fuji Silysia Chemical, Silica 310P, average particle size 1.4 μm) / silica 2 (manufactured by Mizusawa Chemical Industry, Mizukasil P73, average particle size 2.5 μm) = 94.0 / 4.5 / 1.5 (mass ratio), and melt-kneaded under the conditions of cylinder temperature 230 ° C to 270 ° C, screw rotation speed 200 rpm, and discharge rate 10 kg / hour. The obtained melt-kneaded product was pelletized and vacuum dried (80 ° C × 24 hours). Thus, silica master E was obtained. The relative viscosity of the silica master was 3.0.

[0091] [Table 1]

[0092] 2. Examples and Comparative Examples A film was produced using each of the raw materials shown in 1. above.

[0093] Example 1 As the composition of the polyamide resin film, 97.5% by mass of polyamide resin (raw material B1) polymerized only with C-CL and 2.5% by mass of silica masterbate were mixed and melt-kneaded in an extruder, fed to a T-die and discharged in a sheet shape, wound around a metal drum adjusted to 20 ° C, cooled and wound up to obtain an unstretched film with a thickness of about 150 μm. Next, the obtained unstretched film was immersed in a moisture adjustment tank adjusted to 50 ° C for 1 minute, and then the end was held with a clip of a tenter-type simultaneous biaxial stretching device, and simultaneously biaxially stretched at a stretch ratio of 3.0 times in the MD direction and 3.3 times in the TD direction under the condition of 180 ° C. Then, the film was heat-treated at 201 ° C for 4 seconds with a relaxation rate of 5% in the TD direction, and then slowly cooled to room temperature, and corona discharge treatment was performed on one side. Then, the film was wound up to obtain a biaxially stretched polyamide resin film with a thickness of 15 μm. The total regenerated ratio in this film was 97.5% by mass. The moisture content of the unstretched film was 5% by mass.

[0094] Example 2 A biaxially stretched polyamide resin film having a thickness of 15 μm was obtained in the same manner as in Example 1, except that the polyamide resin (raw material B5) in Table 1 was used in an amount of 97.5 mass% as the composition of the polyamide resin film. The total recycled content in this film was 97.5 mass%.

[0095] Examples 3, 5, and 13 A biaxially stretched polyamide resin film having a thickness of 15 μm was obtained in the same manner as in Example 1, except that the polyamide resin (raw material B4), (raw material B3), or (raw material B2) in Table 1 was used at 97.5% as shown in Table 2. The total recycled ratios in this film were 87.8 mass%, 39.0 mass%, and 19.5 mass%, respectively.

[0096] Examples 4, 11, and 18 The composition of the polyamide resin film was determined by blending the polyamide resin (raw material B1) and polyamide resin (raw material C) in Table 1 in the ratio shown in Table 2, and a biaxially oriented polyamide resin film having a thickness of 15 μm was obtained in the same manner as in Example 1, except that 97.5% of this resin was used.

[0097] Examples 6, 7, 9, 10, 16, and 17 The composition of the polyamide resin film was determined by blending the polyamide resin (raw material B1) and polyamide resin (raw material C) in Table 1 and the remelted resin (raw material D) in the ratios shown in Table 2, and using 97.5% by mass of this resin. In the same manner as in Example 1, a biaxially oriented polyamide resin film having a thickness of 15 μm was obtained.

[0098] Example 8 The composition of the polyamide resin film was determined by blending the polyamide resin (raw material B3) in Table 1 and the remelted resin (raw material D) in the ratio shown in Table 2, and a biaxially oriented polyamide resin film having a thickness of 15 μm was obtained in the same manner as in Example 1, except that 97.5% by mass of this resin was used.

[0099] Examples 14 and 15 The composition of the polyamide resin film was determined by blending the polyamide resin (raw material B2) in Table 1 and the remelted resin (raw material D) in the ratio shown in Table 2, and a biaxially oriented polyamide resin film having a thickness of 15 μm was obtained in the same manner as in Example 1, except that 97.5% by mass of this resin was used.

[0100] Example 12 As the composition of the polyamide resin film, the polyamide resin (raw material B1) and the polyamide resin (raw material C) in Table 1 were blended in the ratios shown in Table 2, and 97.5% by mass of this resin and 2.5% by mass of silica masterbate were mixed to obtain an unstretched film in the same manner as in Example 1. Next, the unstretched film was stretched 2.8 times in the MD direction with a temperature-controlled roll at 55 ° C., and then held with a clip and stretched at a stretch ratio of 3.7 times in the TD direction under conditions of 185 ° C. (sequential biaxial stretching). Thereafter, the film was heat-treated at 201 ° C. for 4 seconds with a relaxation rate of 5% in the TD direction, slowly cooled to room temperature, and corona discharge treatment was performed on one side. Thereafter, the film was wound up to obtain a biaxially stretched polyamide resin film with a thickness of 15 μm. The total regenerated ratio in this film was 19.5% by mass. In addition, the moisture content of the unstretched film was 0.5% by mass.

[0101] Example 19 A two-type three-layer film with a thickness ratio of 1:1:1 was produced as a polyamide resin film. As the intermediate layer, a resin in which 25% by mass of polyamide resin (raw material C) in Table 1 and 75% by mass of remelted resin (raw material D) were mixed was arranged. As both outer layers, polyamide resin (B3) in Table 1 was arranged. An unstretched film was obtained in the same manner as in Example 1, except that 2.5% by mass of silica masterbatch was mixed into each layer and co-extruded, and a biaxially stretched polyamide resin film with a thickness of 15 μm was obtained by simultaneous biaxial stretching. The total recycled ratio in this film was 50.4% by mass.

[0102] Comparative Example 1 A biaxially stretched polyamide resin film having a thickness of 15 μm was obtained in the same manner as in Example 1, except that the polyamide resin (B6) in Table 1 was used in an amount of 97.5 mass % as the composition of the polyamide resin film.

[0103] Comparative Example 2 A biaxially stretched polyamide resin film having a thickness of 15 μm was obtained in the same manner as in Example 1, except that the remelted resin (D) was used in an amount of 97.5 mass % as the composition of the polyamide resin film.

[0104] Comparative Example 3 A biaxially stretched polyamide resin film having a thickness of 15 μm was obtained in the same manner as in Example 12, except that the remelted resin (D) was used in an amount of 97.5 mass % as the composition of the polyamide resin film.

[0105] Comparative Examples 4 and 5 The composition of the polyamide resin film was determined by blending polyamide resin (C) and remelted resin (D) in the ratio shown in Table 2. Except for using 97.5% by mass of this resin, a biaxially oriented polyamide resin film having a thickness of 15 μm was obtained in the same manner as in Example 1.

[0106] Comparative Example 6 A biaxially stretched polyamide resin film having a thickness of 15 μm was obtained in the same manner as in Example 1, except that the polyamide resin (C) was used in an amount of 97.5 mass % as the composition of the polyamide resin film.

[0107] Comparative Example 7 The composition of the polyamide resin film was a mixture of 97.5% by mass of polyamide resin (C) and 2.5% by mass of master chip (E), which were melted and kneaded in an extruder, fed to a T-die and discharged in the form of a sheet, wound around a metal drum whose temperature was controlled at 20°C, cooled, and wound up to obtain an unstretched film with a thickness of about 150 μm. At this time, the actual temperature of the metal drum whose temperature was controlled at 20°C varied, and the crystallinity of the unstretched film also varied. A biaxially stretched polyamide resin film with a thickness of 15 μm was obtained in the same manner as in Example 1 except for this. The thickness accuracy of the obtained film was confirmed to exceed ±15% in some places.

[0108] [Table 2]

[0109] Test Example 1 The following physical properties were examined for the raw polyamide resins (raw materials B1 to D) and the films obtained in each of the Examples and Comparative Examples. The results are shown in Table 3. For each measurement, samples were left in an environment of 23°C temperature and 50% RH for 2 hours or more, and measurements were performed in an atmosphere of 23°C temperature and 50% RH.

[0110] (1) Relative viscosity ηR The raw polyamide resins (raw materials B1 to D) and the films obtained in each of the Examples and Comparative Examples were used as samples, and the relative viscosity of the sample solutions (liquid temperature 25°C) dissolved in 96% sulfuric acid to a concentration of 1.0 g / dl was measured using an Ubbelohde viscometer.

[0111] (2) Moisture content The unstretched film after the water absorption treatment or immediately before stretching was sampled, placed in a weighing bottle, and then dried. The mass was calculated from the change in mass before and after drying.

[0112] (3) Caprolactam Monomer Content [Preparation of measurement samples] The raw polyamide resins (raw materials B1 to D) and the films obtained in each Example and Comparative Example were freeze-pulverized, weighed out at 0.5 g, and placed in a 10 ml headspace bottle, to which 10 ml of ultrapure water was added, and the bottle was sealed with a butyl rubber stopper and an aluminum cap, after which extraction was carried out in a boiling water bath (100°C) for 2 hours. After cooling, the bottle was filtered through a 0.45 μm disk filter to prepare a measurement sample. [Creating a calibration curve] 0.1 g of caprolactam was dissolved in 100 ml of ultrapure water to make a 1000 ppm solution, which was further diluted to prepare standard solutions of 100, 50, 20, 10, 5, and 2 ppm, and a calibration curve was created. [HPLC conditions] Apparatus: Hewlett Packard HP1100 HPLC system, column: Waters Pureisil 5 μm C18 120 Å 4.6 mm × 250 mm (40° C.), detector: UV 210 nm, injection volume: 10 μl, flow rate: 0.7 ml / min, elution: methanol / water (volume ratio: 35 / 75) solution for 12 minutes, then switched to methanol / water (volume ratio: 100 / 0) solution over 3 minutes and run for 30 minutes, then switched to methanol / water (volume ratio: 35 / 75) solution over 5 minutes and run for 20 minutes. [Calculation method] The mass of the monomer in the sample was calculated from the monomer concentration of the sample detected under the above conditions, and the value divided by the mass of the measured sample was determined as the amount of monomer extracted (mass %).

[0113] (4) Crystallization temperature Tc and half-width Using a PerkinElmer differential scanning calorimeter (power compensation type DSC8000), 10 mg of the obtained resin was weighed out, heated from room temperature to 260°C at a heating rate of 10°C / min, held at 260°C for 10 minutes, and then cooled to 100°C at a heating rate of 10°C / min to measure the crystallization temperature. In a DSC curve with heat flow (mW) on the vertical axis and temperature on the horizontal axis, the peak top temperature during cooling was defined as Tc (°C), a baseline was drawn from the high temperature side, and the interval between two points at 1 / 2 the absolute value of Tc was defined as the half-width (°C).

[0114] (5) Terminal amino group content The films obtained in each of the Examples and Comparative Examples were dissolved in a solvent (phenol / ethanol=4 / 1 volume ratio), and a fixed amount of 0.02N hydrochloric acid was added, followed by back titration with 0.02N sodium hydroxide solution.

[0115] (6) Terminal carboxyl group content The films obtained in each of the Examples and Comparative Examples were dissolved in benzyl alcohol at 180° C., and a phenolphthalein indicator was added thereto, followed by titration with a 0.02 N ethanol solution of potassium hydroxide.

[0116] (7) Evaluation of the number of missing dots in half-tone printing at 10% gradation and evaluation of expandability at 40% gradation [Printing process] The printing ink was made by mixing Rio Alpha R39 indigo (manufactured by TOYOINK) with diluent NKFS102 (manufactured by TOYOINK) and adjusting the viscosity (23°C) to 15 seconds using Zahn cup #3. The printing roll film was made by slitting the film at positions 500 mm left and right from the center in the TD direction. After applying the ink to the film using a helio-engraved gradation change plate for gravure printing, it was dried at 50°C for 10 seconds and wound up to make the printing film. This gradation change plate is helio-engraved in the MD direction in the order of gradation 10%, 20%, 30%, 40%, and 100% with 175 lines (175 halftone dots per inch). The depth of each gradation is 2.5 μm, 5.0 μm, 7.5 μm, 10.0 μm, and 32.0 μm, respectively, and the printing length of each gradation in the MD direction is 60 mm, and the printing width in the TD direction is 0.8 m. Rio Alpha R39 Indigo is mainly composed of 10% pigment by weight, 15% synthetic resin by weight, 2.5% silica by weight, 30% ethyl acetate by weight, 15% isopropyl alcohol by weight, 10% propyl acetate by weight, 10% propylene glycol monomethyl ether by weight, and 5% n-propyl alcohol by weight. The diluent NKFS102 mainly consists of 50% by mass of ethyl acetate, 35% by mass of propyl acetate, 10% by mass of isopropyl alcohol, and 5% by mass of n-propyl alcohol. [Evaluation of number of dead dots] A total of 10 samples were taken from the 10% gradation area of ​​the printed film, and magnified 8 times using a stereo microscope (ZEISS SteREO Discovery.V12) to measure a total area of ​​1000 mm2 (20 mm in MD × 50 mm in TD). 2 The number of missing dots (i.e., areas that could not be printed) was counted within the range (a total of 47,500 dots). The same evaluation was performed on 10 sampled locations, and the value with the greatest number of missing dots among all 10 locations is shown in Table 3. The outline of the measurement method is shown in Figure 1. In the printed part with 10% gradation, the MD direction was evaluated at the remaining 20 mm portion excluding the top and bottom 20 mm portions, and the TD direction was evaluated at a total of 10 points at 30 mm intervals, starting from the position 100 mm from the end of the film and counting the 50 mm portion as the first point. That is, as shown in Figure 1, 10 points in the measurement areas a to j of 20 mm x 50 mm were evaluated. The number of missing dots should be 100 or less out of the total (47,500) dots, but it is particularly preferable to have 80 or less, more preferably 70 or less, and most preferably 60 or less. If the number exceeds 100, even in the low gradation area, unevenness can be visually confirmed with the naked eye, and individual differences in the pattern can be felt, and it may be judged as a printing defect. [Scalability evaluation] A 40% gradation portion of the printed film was magnified 20 times using a stereo microscope (ZEISS SteREO Discovery.V12), and the dot shape was observed and the dot diameter was measured at 10 arbitrary points. The dots were then rated on a three-point scale according to the following evaluation criteria. (Evaluation Criteria) ⊚: No problem is observed in the dot shape, and the ratio of the minimum to maximum dot diameter is between 0.9 and 1. .largecircle.: No problem is observed in the dot shape, and the ratio of the minimum to maximum dot diameter is 0.85 or more and less than 0.9. .DELTA.: The dot shape is slightly distorted, and the ratio of the minimum to maximum dot diameter is 0.75 or more and less than 0.85. × . . . The dot shape is distorted, the dot size is uneven, and the ratio of the minimum to maximum dot diameter is less than 0.75.

[0117] (8) Impact strength (J) The samples were cut out from the central portion of the obtained polyamide resin film and from the left and right portions 50 cm from the central portion in the TD direction, each having a width of 10 cm and a length of 150 cm. The impact strength was measured 15 times each using a film impact tester manufactured by Toyo Seiki Seisakusho Co., Ltd., with a 1 / 2 inch hemispherical head, by clamping and fixing the samples in a jig having a circular hole of 50 cmφ. The ratio of the minimum and maximum values ​​of the impact strength (minimum value / maximum value) is shown in Table 2. The ratio is preferably 0.5 to 1.0, more preferably 0.6 to 1.0, and even more preferably 0.7 to 1.0. If the ratio is less than 0.5, it is considered that there is a partial decrease in the impact resistance of the film, which is not practically preferable.

[0118] (10) Tensile elongation (%) The tensile elongation was measured using a Shimadzu DSS-500 Autograph in accordance with Japanese Industrial Standard JIS K7127. The central part of the obtained polyamide resin film in the TD direction was cut into a width of 10 mm and a length of 150 mm in the MD direction to prepare a sample. The measurement was performed under the conditions of a measurement length of 100 mm (distance between grippers) and a pulling speed of 500 mm / min, and the elongation was calculated using the following formula. Tensile elongation (%) = gripper movement distance at break (mm) / original gripper distance (100 mm) x 100

[0119] (11) Haze (%) The haze was measured at the center of the film in the TD direction according to Japanese Industrial Standard JIS K7136 using a Nippon Denshoku haze meter (NDH4000).

[0120] (12) Wetting tension (mN / m) The corona-treated surface of the film was measured using wet tension test mixture No. 36.0-54.0 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in accordance with Japanese Industrial Standard JIS K6768. The wet tension was measured at five positions at 200 mm intervals from the center to both ends in the TD direction. This was measured every 1 m in the MD direction, for a total of 50 positions. The minimum and maximum values ​​of the wet tension measurements at the 50 positions are shown in Table 3. A wet tension of 44 mN / m or more is usually practical, but 46 mN / m or more is particularly preferable.

[0121] (13) Bag rupture resistance (drop test) [Lamination process] A urethane adhesive (DIC Corporation, Dick Dry LX-401A / SP-60) was applied to the surface of the film at a dry coating weight of 3.0 g / m 2 After that, a heat treatment was performed at 80° C. Then, an unstretched polyethylene film (TUX MCS, 50 μm, manufactured by Mitsui Chemicals Tocello Co., Ltd.) was dry laminated on the adhesive surface after the heat treatment at a nip pressure of 490 kPa on a metal roll heated to 80° C. Furthermore, the adhesive was subjected to aging as recommended to obtain a laminate film. [Bag sample production] The laminate film thus produced was cut into two pieces measuring 200 mm x 300 mm, the polyethylene films were joined together, and the three sides were heat-sealed at a width of 10 mm to produce a three-sided bag. The sealing conditions were 160°C x 1 second. The three-sided bag thus produced was filled with 1000 ml of water, the air inside the bag was released, and the remaining side was heat-sealed at a width of 10 mm, after which 10 ml of air was enclosed using a syringe, and the bag was heat-sealed again to produce a test sample. The sealing conditions were 160°C x 1 second. By introducing a small amount of air, the damage to the bag caused by water was greater, and the test was conducted under harsher conditions than when only water was used. [Dropped bag test] The prepared test sample was dropped from a height of 1.2 m above a horizontally placed 0.5 mm thick smooth stainless steel plate (SUS plate) so that its bottom end was 1.2 m above the SUS plate so that one film side of the test sample hit the SUS plate. Test A was then performed alternately, and the test sample was dropped so that one short side of the test sample hit the SUS plate, until the test sample broke. The number of drops of Tests A or B until the test sample broke was measured. Each test sample had two film surfaces and two short sides, and each sample was dropped so that the same film surface or the same short side struck the SUS plate. The test was performed in an atmosphere of 23°C and 50% RH, with three samples (n=3), and the minimum number of drops required before the bag broke is shown in Table 3. Under these conditions, the number of drops required before the bag broke is 50 or more in practical terms, with 60 or more being particularly preferred, and 70 or more being even more preferred.

[0122] [Table 3]

[0123] As is clear from these results, the biaxially stretched polyamide resin films of Examples 1 to 19 were polyamide resin films using polyamide resins obtained by polymerizing recycled monomers, and therefore had excellent printability in low gradation areas, controlled variations in impact strength, and no problems with general physical properties such as film elongation, wettability, and haze. As shown by the drop bag test, the practical performance was also excellent.

[0124] In Comparative Example 1, the relative viscosity of the raw materials used was low, and the mechanical properties of the obtained film were poor, especially the impact strength. This caused a cutting trouble in the next process, and normal printing was not possible.

[0125] Comparative Examples 2, 4, and 5 did not contain polyamide resin polymerized from recycled monomers, and had a large amount of terminal amino or carboxyl groups derived from the remelted resin, which caused the crystallization rate of the film raw material to increase, resulting in localized variation in the crystallization state of the surface. This resulted in a decrease in the printability of low gradation areas, and in the bag drop test, this led to a local decrease in adhesion, making the bag more likely to break. In addition, a decrease in elongation and variation in impact strength were observed, which are thought to be due to impurities in the remelted resin.

[0126] In Comparative Example 3, the same raw material as in Comparative Example 2 was used, but the amount of monomer in the film increased as a result of successive stretching. This resulted in a local decrease in printability in low gradation areas, and similarly worsened the results of the drop bag test. There was also a decrease in elongation and variation in impact strength, which are thought to be due to impurities in the remelted resin.

[0127] Comparative Example 6 is a film obtained using a polyamide resin consisting only of virgin monomers. Although no problems were observed in the general physical properties and practical performance, the reproducibility of the printability of low gradation areas was inferior to that of the film obtained using recycled monomers.

[0128] In Comparative Example 7, a polyamide resin consisting of only virgin monomers was used, but the temperature control of the casting roll was insufficient, and the surface crystallinity of the unstretched film varied, which resulted in the crystallinity of the stretched film surface also varying, resulting in a decrease in printability of low gradation areas. In addition, there were some parts where the film thickness accuracy after stretching exceeded 15%, which resulted in variations in impact strength and elongation.

Claims

1. A method for producing a polyamide resin film, comprising the steps of: (1) a step of producing a monomer from a raw material for depolymerization (A); (2) A step of producing a polyamide resin (B) by polymerizing a raw material containing the monomer; (3) A step of refining the polyamide resin (B) (4) A step of producing an unstretched film using a starting material containing the refined polyamide resin (B) and then stretching the unstretched film. A method for producing a polyamide resin film, comprising:

2. The method of claim 1 , wherein the monomer comprises ε-caprolactam.

3. The method according to claim 1, further comprising a step of adjusting the moisture content of the unstretched film to 2 to 10% by mass prior to the stretching.

4. The method according to claim 1, wherein a part of the starting material contains a remelted resin obtained by melting a polyamide resin (excluding the polyamide resin (B)), and the content of the remelted resin is 1 mass% or more.

5. The method according to claim 1, wherein the refined polyamide resin (B) has a relative viscosity ηR of 2.5 to 4.

5.

6. The method according to claim 1, wherein the raw material for depolymerization (A) is at least one of polyamide 6 resin and its oligomer.

Citation Information

Patent Citations

  • Clothing product made of nylon and method for recycling the same

    JP1995310204A

  • Recovery of epsilon-caprolactam

    JP1999035554A

  • Sheetlike article and recycling method thereof

    JP2001058366A

  • Oriented polyamide film

    JP2002173598A

  • Laminated biaxially oriented polyamide film

    JP2010253713A